MHD peristaltic motion of a maxwell fluid in axisymmetric tube - Zakaria, Khalid Ahmed (The Physical Society of Japan, 2012)
Peristaltic motion of a Maxwell fluid in an axisymmetric tube with a sinusoidal wave train traveling along the wall is studied under the long wavelength and low Reynolds number approximation. This analysis can model the transport of blood in small vessels by using the viscoelastic Maxwell model. The fluid is electrically conducting fluid in the presence of a magnetic field. Analytical solutions for the stream velocity, the axial velocity and the pressure gradient have been obtained. The effects of the Hartman number, the flow rate and the amplitude ratio on the pressure gradient, the pressure rise and the frictional force per wavelength are discussed through numerical computations.